Visible light polymerization of epoxy monomers using an iodonium salt with camphorquinone/ethyl-4-dimethyl aminobenzoate - Schroeder, Walter Fabian (2013)
A visible light initiator system for the photoinduced cationic polymerization of epoxymonomers is reported. The system consists of camphorquinone (CQ) in combination with ethyl-4-dimethyl aminobenzoate (EDMAB) and a diaryliodonium salt (Ph2ISbF6.) The three-component system efficiently photoinitiates the polymerization of monomers containing an epoxycyclohexane group, 3,4-epoxycyclohexylmethyl 3’,4’-epoxycyclohexane carboxylate (UVR) and 1,3-bis(3,4-epoxycyclohexyl-2-ethyl),1,1,3,3-tetramethyldisiloxane (SIB), under irradiation with blue light (λ = 467 nm). Very rapid photopolymerization resulted from irradiation of SIB containing Ph2ISbF6 in combination with CQ and better results were obtained in the presence of EDMAB. On the other hand, no polymerization was detected after irradiation of UVR photoactivated with Ph2ISbF6 and CQ. However, this monomer polymerized readily and to high conversion when EDMAB was present. Moreover, almost complete conversion of UVR occurs in the absence of external heating. The polymer resulting from UVR displayed higher values of compressive and flexural properties than the polymer prepared from SIB. This is explained in terms of a higher density of crosslinking points in UVR which is accompanied by a lower content of non-reacted monomer; this has a plasticizing effect on the hardened material.